Molecular identification of the main allergens present in household dust of asthmatic patients - Ferreira Moreira, Hyngrid Carolinne Soares; Santos, Sâmia Melo; Alves, Matheus Silva; Pereira Bena, Maryangela Godinho; Lopes, Giselmo Pinheiro; Bomfim, Maria Rosa Quaresma; Lima Neto, Lídio Gonçalves; Falcai, Angela (Ciência e Natura, 2022)
The main aeroallergens present in house dust are the mites,Dermatophagoidespteronyssinus (Derp) andDermatophagoidesfarinae (Derf), and cockroaches,Periplanetaamericana (Pera). Objective: This work aims to genetically identify the allergens Derp, Derf, and Pera in household dust of asthmatic patients. Materials and methods: 29 patients, aged between 3 and 17 years, were classified as asthmatic or non-asthmatic according to the International Study of Asthma and Allergies in Childhood(ISAAC). Subjectscompleted a complementary questionnaire and skin hypersensitivity tests were performed. House dust was collected from these patients, filtered, and then DNA was extracted. Polymerase chain reactions were performed to identify Derp, Derf, and Pera in the samples. Results: There was an association between Pera sensitization and onset of asthma. There was also an association between the presence of Derp in the home of asthmatic patients and the worsening of symptoms, such as wheezing in the chest and allergic rhinitis. An association between the presence of Derf in house dust of asthmatic patients and the symptoms of allergic rhinitis was found. These data suggest that cockroach sensitization is a predominant factor in asthmatic children and the presence of mite allergens contributesto the worsening of asthma symptoms.